2021
DOI: 10.3390/foods10112803
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Microwave-Assisted Green Method for Enhanced Solubilization of Water-Soluble Curcuminoids Prepared Using Steviol Glycosides

Abstract: In this study, the optimization and modeling of microwave-assisted extraction (MAE) of water-soluble curcuminoids prepared using novel steviol glycosides (SGs) was carried out using four independent process variables at varying levels—X1: microwave power (50–200 W), X2: stevioside concentration (50–200 mg/mL), X3: curcumin concentration (20–200 mg/mL), and X4: time (1–10 min)—in response surface methodology configuration. Moreover, the effects of stevioside, as the most cost-effective natural solubilizer, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Analytical and in silico study was of the inclusion complexes between tropane alkaloids atropine and scopolamine with cyclodextrins [87]. The most recent study by Ko et al (2021) also highlighted the use of steviol glycosides for the conversion of poorly water soluble curcumin into water soluble curcuminoids (Curcumin-steviol glycosides complex) for antiviral theapy. Moreover, the author reported the novel method of Microwave-assisted extraction and stated that by using in conjunction with the Curcumin-steviol glycosides complex several folds enhanced solubility (11 mg/L to 1320 mg/L) was achieved [53].…”
Section: Complex Formationmentioning
confidence: 99%
“…Analytical and in silico study was of the inclusion complexes between tropane alkaloids atropine and scopolamine with cyclodextrins [87]. The most recent study by Ko et al (2021) also highlighted the use of steviol glycosides for the conversion of poorly water soluble curcumin into water soluble curcuminoids (Curcumin-steviol glycosides complex) for antiviral theapy. Moreover, the author reported the novel method of Microwave-assisted extraction and stated that by using in conjunction with the Curcumin-steviol glycosides complex several folds enhanced solubility (11 mg/L to 1320 mg/L) was achieved [53].…”
Section: Complex Formationmentioning
confidence: 99%
“…Following this trend, we recently reported a new method for increasing the solubility of curcuminoids using stevioside, a known natural solubilizer, and a microwave-assisted method. Here, water-soluble curcuminoids (named C—S/M) prepared using stevioside are made in nanoparticle form (average particle size of approximately 190 nm) [19] . Importantly, recent studies demonstrated that using biomaterials encapsulated in stevioside can usually improve bioactivity, stability, and cell-to-nanoparticle interaction [20] , [21] .…”
Section: Introductionmentioning
confidence: 99%